M266 Development Of An Idiopathic Pulmonary Fibrosis (ipf) Patient Reported Outcome Measure (prom): An Iterative Approach To Item Generation. (10th November 2014) - Russell, AM; Sanderson, T; Fleming, S; Wells, AU; Maher, TMM; Cullinan, TP
Abstract : Introduction: Patients diagnosed with IPF experience debilitating symptoms which impact upon quality of life. To date there is no curative treatment and the tolerability andefficacy of existing andemergent therapies require further evaluation. We are developing a new concise IPF-PRoM (according to FDA criteria¹) for use as a primary endpoint in studies exploring treatments of symptoms associated with IPF andas a secondary endpoint in clinical/therapeutic trials. Robust item generation is fundamental to the development of the IPF-PRoM reflecting what is important to patients and ensuring saturation is reached. Methodology: Domains and items were identified in existing symptom and quality of life measures used in IPF studies reported in the literature 5 focus groups were held at one of 3 UK centres. 28 patients (18 male) stratified for disease severity according to Composite Physiological Index (CPI) participated. Transcripts underwent inductive analysis and data was coded using NVIVO 10 ©QSR software Expert Opinion was sought from 10 ILD physicians utilising the Nominal Group technique. The importance of each descriptor identified in the literature was rated and then ranked according to overall importance. The top 5 were noted anddiscussed. Descriptors defined by focus group participants (n = 9) were added and the process repeated A multidisciplinary Research Support Group including patient and carer representatives contribute to the analysis at each stage and have the authority to mandate for the inclusion of 'grey' items. Interim results: A validation list applied to existing measures identified 208 items for inclusion. Systematic coding and recoding within NViVo reduced 28 categories initially identified to 10. Fatigue is identified as a dominant theme in patients with CPI ≥ 45 andmedication availability/impacts has emerged as a significant category in all groups. ILD experts place importance upon breathlessness and emotional and mental well-being (Table 1). Discussion: This methodological approach to item generation will enhance the content validity of the IPF-PROM instrument. Items generated to date will be modified further by 80 patients from 4 UK centres and 20 ILD physicians participating in 3 rounds of a Qualtrics Delphi survey. This study is ongoing. 1 http://www.fda.gov/downloads/Drugs/Guidances/UCM193282.pdf